CORRELATION BETWEEN BIRTH BODY WEIGHT AND THE OCCURRENCE OF PERINEUM RUPTURE OF SPONTANEOUS CHILDBIRTH IN MOTHER AND CHILD LOCAL SPECIAL HOSPITAL (RSKDIA) OF SITI FATIMAH MAKASSAR - rahmatullah rahmatullah (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2019)
Introduction: Childbirth is the process of movement of fetus, placenta, and membrane from uterus through birth canal. Childbirth very frequently causes perineum rupture. This research aims to determine the correlation between birth body weight and the occurrence of perineum rupture in Mother and Child Local Special Hospital (RSKDIA) of Siti Fatimah, Makassar. Method: The research was an analytic observational study using cross sectional study approach. The research design was the measurement of birth body weight and perineum rupture or the observation of independent and dependent variables. The observation of objects was only conducted once at a time. The sample was determined using purposive sampling technique consisting of 48 respondents. Correlation test used chi-square test with kolmogorov-sminov with the significant level of a < 0.05. Result: The results of the research indicate that the babies having low birth body weight with the occurrence of rupture is 4.2%; the ones having normal birth body weight with the occurrence of rupture is 47.9%, and the ones having big body weight with the occurrence of rupture is 6.3%. This indicates that there is a correlation between birth body weight and the occurrence of perineum rupture in Mother and Child Local Special Hospital (RSKDIA) of Siti Fatimah, Makassar. Conclusion: It is concluded that birth body weight and the occurrence of perineum rupture indicates the result of statistic test of p=0.002. Therefore, it is hoped for pregnant women to increase more their awareness to have ante natal care so that medical staff can monitor the estimated fetal weight to reduce the occurrence of rupture in the mothers.